Contested sovereignty in Mozambique: The dilemmas of aid dependence - Paolo De Renzio; Joseph Hanlon (University of Oxford, Global Economic Governance Programme (GEG), 2007)
Mozambique has been seen by donors as a success story of peace, stability and growth since the end of its devastating war in 1992. Indeed, it has become increasingly important to the international community as one of the few successes in Africa. Donors have invested a substantial amount of resources and effort in support of Mozambique's economic and political performance, and are understandably committed to sustaining it for as long as possible. Mozambique continues to be highly aid dependent (see Figure 1), but is considered as a model by the Bretton Woods institutions, having consistently met most donor demands, while at the same time growing at an official average rate of about 8% per year since 1997 (EIU 2006). During the same period, poverty declined, but at a much slower rate. Given its privileged status among donors, Mozambique has also become a model and a testing ground for so called "new aid modalities", such as sector and General Budget Support (GBS), in the context of the shifting international debates around aid effectiveness, enshrined in the Paris Declaration of March 2005 (OECD 2005). This has included an innovative mechanism for monitoring donor performance on harmonisation and alignment of their support to the country, called the Programme Aid Partners' Performance Assessment Framework (PAP's PAF), discussed in more detail later in this paper.
Keywords: 330